Regulatory policy transformation in conditions of nonstationary economy in eastern European countries: practical approach - Abramova, A. S.; Filyppova, S.; Vdovenko, N.; Kotelevets, D.; Lozychenko, O.; Malin, O. (International Journal of Computer Science and Network Security., 2021)
European economic processes have always been the center of public interest. 2010-2019 were characterized by economic development and result achievements in the conditions of information flows exchange and digital changes. However, the pandemic effects of Covid-19 have negatively influenced economic activity, causing significant uncertainty in subsequent economic processes, which were reflected in GDP trends and determined the non-stationary economic conditions. And although the first half of 2021 marks GDP growth, the economic recovery, projected in the traditional scenario, is not enough to reach the precrisis level of production again. The purpose of the study is to identify the effects on European countries economic development and to develop proposals for directions and instruments of regulatory policy transformation, which would take into account the current non-stationary economic conditions. Achieving the goal led to the usage of scientific and practical methods of cognition, including the method of deduction and induction, system analysis, synthesis, generalization, mathematical methods and models. The study characterizes the nature of non-stationary economic development and identifies the need for regulatory influence to ensure further economic growth. The analysis proposes to use GDP as an indicator of economic processes dynamics with the specification of system of direct and indirect influence factors using a multifactor dynamic model. The assessment of depth and nature of their impact allowed to divide them by the stationary and non-stationary criterion. On the basis of received values the directions of regulatory policy transformation in the conditions of non-stationary economic processes have been offered.
Keywords: non-stationary economy, regulatory policy, GDP, econometric modeling, influence factors, regulation